Strengthening Tolerance Character in Aqidah Akhlak Learning at MTs Kayu Aro Lindung Jaya - Permana, Defwan; Usman, Usman; Jalwis, Jalwis (Institut Agama Islam Negeri Kerinci, Indonesia, 2024)
This study aims to analyze the role of teachers in strengthening students’ tolerance character through Akidah Akhlak learning at MTsS Kayu Aro Lindung Jaya. The urgency of this research lies in the increasing importance of tolerance education in multicultural societies, particularly in schools where students from different cultural and ethnic backgrounds interact on a daily basis. Tolerance is not only a social necessity but also a moral value that must be systematically cultivated through education. A qualitative descriptive approach was employed to explore this phenomenon in depth. Data were collected using observations, interviews, and documentation to capture comprehensive perspectives from multiple stakeholders. The research participants consisted of one Akidah Akhlak teacher, the school principal, the deputy of curriculum, and ten students representing different ethnic backgrounds. The results indicate that Akidah Akhlak learning was implemented through an integrative and holistic approach that combined theoretical knowledge with practical moral guidance. The tolerance values emphasized include respect for religious, cultural, and ethnic differences, appreciation of diverse opinions, recognition of others’ beliefs, and collaboration across diversity. These values were reinforced through classroom activities, group discussions, and extracurricular programs. Strengthening tolerance was supported by teachers’ role modeling, family upbringing, the school environment, and social experiences. The internal impacts included students’ self-awareness, empathy, and conflict resolution skills, while the external impacts contributed to creating a peaceful, harmonious, and inclusive school climate. The findings highlight the strategic role of religious education as a powerful medium for cultivating tolerance and social cohesion in multicultural contexts